Hipertensão pulmonar em pacientes com doença renal crônica dialítica está associada com hipervolemia e inflação - Telini, Wagner Moneda [UNESP] (2015)
Introduction: Pulmonary hypertension (PH) in patients with chronic nephropathy undergoing hemodialysis is related to high mortality. Our group has previously demonstrated an association between hypervolemia and PH in this population. Evidences showing that micro inflammatory state could be induced by chronic volume overload bring us the hypothesis that inflammatory markers might be involved in the pathogenesis of PH in these patients. Aim: to verify an association between PH, hypervolemia and inflammation in chronic hemodialysis patients. Patients and methods: transversal study evaluated patients≥18 yrs in chronic hemodialysis treatment for at least three months. PH was considered as a pulmonary artery systolic pressure > 35 mmHg by echocardiography exam. According to the results, patients were allocated in one of the following groups PH or non-PH. Bioimpedance, echocardiographic parameters, C-reactive protein (CRP), acid alpha 1 glycoprotein (AGP) and B-type natriuretic peptide (BNP) were evaluated. Comparisons between groups were considered significant at p ˂ 0.05. Results: 119 patients were selected, 64 men and 55 women, with mean age of 58 ± 14.2 years; 23 patients had PH (19%). Both groups were homogeneous in terms of age, gender and time in hemodialysis. However, they differed in terms of left atrium diameter (46 + 5.3mm in PH group vs 42 + 4.8mm in non-PH group, p <0.01), fluid overload (-0,2 + 3.98L vs -2.4 + 2.79L, p<0.01), BNP (898 (1232) pg/mL vs 267 (424) pg/dL, p<0.01) and inflammatory markers: AGP (140 + 32mg/dL vs 116 + 30.5mg/dL, p<0.01) and CRP (2.57 (3.91) mg/dL vs 1.48 (1.28) mg/dL, p= 0.02). A model of logistic regression was elaborated to verify the isolated effect of the parameters evaluated. Thus, BNP levels, to represent volume, and AGP, to represent inflammation, were selected. As a result, BNP as well as AGP showed statistically significant association: AGP (OR 1.023; IC 95% 1.005-1.041); BNP (OR 1.001;...